2017
DOI: 10.1186/s12974-017-0973-8
|View full text |Cite
|
Sign up to set email alerts
|

The potassium channel KCa3.1 constitutes a pharmacological target for astrogliosis associated with ischemia stroke

Abstract: BackgroundReactive astrogliosis is one of the significantly pathological features in ischemic stroke accompanied with changes in gene expression, morphology, and proliferation. KCa3.1 was involved in TGF-β-induced astrogliosis in vitro and also contributed to astrogliosis-mediated neuroinflammation in neurodegeneration disease.MethodsWild type mice and KCa3.1−/− mice were subjected to permanent middle cerebral artery occlusion (pMCAO) to evaluate the infarct areas by 2,3,5-triphenyltetrazolium hydrochloride st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…It was reported that blockade of KCa3.1 significantly reduced neuronal loss and memory deficits in both APP/PS1 mice and SAMP8 mice [ 11 , 15 ]. Given that neuronal loss and decreased expression of synaptic proteins are likely correlated with the severity of AD [ 30 ], we compared expression levels of the neuron marker NeuN in the brain tissues of APP/PS1 mice with those of KCa3.1 −/− /APP/PS1 mutants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that blockade of KCa3.1 significantly reduced neuronal loss and memory deficits in both APP/PS1 mice and SAMP8 mice [ 11 , 15 ]. Given that neuronal loss and decreased expression of synaptic proteins are likely correlated with the severity of AD [ 30 ], we compared expression levels of the neuron marker NeuN in the brain tissues of APP/PS1 mice with those of KCa3.1 −/− /APP/PS1 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of KCa3.1 channels to CNS function is underscored by a series of studies implicating KCa3.1 in various diseases, including stroke/ischemia [ 32 , 33 ], AD [ 11 , 15 ], traumatic brain injury [ 34 ], and spinal cord injury [ 35 ]. These studies showed that upregulation of KCa3.1 activity can profoundly influence CNS pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pharmacological agonists, astrocyte TRPV4 channels respond to epoxyeicosatrienoic acid (Baylie & Brayden, ), hemodynamic and mechanical stimuli (e.g., pressure, stretch, and swelling; Jo et al, ; Kim et al, ). While evidence support enhanced TRPV4 channel function in ischemia (Butenko et al, ; Rakers, Schmid, & Petzold, ; Yi et al, ), little is known on their function in hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence support enhanced TRPV4 channel function in ischemia (Butenko et al, 2012;Rakers, Schmid, & Petzold, 2017;Yi et al, 2017), little is known on their function in hypertension.…”
mentioning
confidence: 99%